Five-Year Survival of Children With Chronic Critical Illness in Australia and New Zealand*. Issue 9 (September 2015) - Namachivayam, Siva P.; Alexander, Janet; Slater, Anthony; Millar, Johnny; Erickson, Simon; Tibballs, James; Festa, Marino; Ganu, Subodh; Segedin, Liz; Schlapbach, Luregn J.; Williams, Gary; Shann, Frank; et al.
<x xml:space="preserve">Abstract</x> Objective: Outcomes for children with chronic critical illness are not defined. We examined the long-term survival of these children in Australia and New Zealand. Design: All cases of PICU chronic critical illness with length of stay more than 28 days and age 16 years old or younger in Australia and New Zealand from 2000 to 2011 were studied. Five-year survival was analyzed using Kaplan-Meir estimates, and risk factors for mortality evaluated using Cox regression. Setting: All PICUs in Australia and New Zealand. Patients: Nine hundred twenty-four children with chronic critical illness. Intervention: None. Measurements and Main Results: Nine hundred twenty-four children were admitted to PICU for longer than 28 days on 1, 056 occasions, accounting for 1.3% of total admissions and 23.5% of bed days. Survival was known for 883 of 924 patients (95.5%), with a median follow-up of 3.4 years. The proportion with primary cardiac diagnosis increased from 27% in 2000–2001 to 41% in 2010–2011. Survival was 81.4% (95% CI, 78.6–83.9) to PICU discharge, 70% (95% CI, 66.7–72.8) at 1 year, and 65.5% (95% CI, 62.1–68.6) at 5 years. Five-year survival was 64% (95% CI, 58.7–68.6) for children admitted in 2000–2005 and 66% (95% CI, 61.7–70) if admitted in 2006–2011 (log-rank test, p = 0.37). After adjusting for admission severity of illness using the Paediatric Index of Mortality 2 score, predictors for 5-year mortality included bone marrow transplant (hazard ratio, 3.66; 95% CI, 2.26–5.92) and single-ventricle physiology (hazard ratio, 1.98; 95% CI, 1.37–2.87). Five-year survival for single-ventricle physiology was 47.2% (95% CI, 34.3–59.1) and for bone marrow transplantation 22.8% (95% CI, 8.7–40.8). Conclusions: Two thirds of children with chronic critical illness survive for at-least 5 years, but there was no improvement between 2000 and 2011. Cardiac disease constitutes an increasing proportion of pediatric chronic critical illness. Bone marrow transplant recipients and single-ventricle physiology have the poorest outcomes.